Poselstwo Petera Hoffmanna do Afanasija Ordina‑Naszczokina (styczeń—luty 1660) Przyczynek do zagadnienia polityki brandenburskiej wobec Moskwy - Augusiewicz, Sławomir (Wieki Stare i Nowe, 2019)
A persistent pursuit of the Brandendburg policy toward Moscow during the Second Northern War was to maintain peaceful relations — for the sake of the security of Ducal Prussia located near the theatre of war. This ambition was supposed to be also served by Peter Hoffmann’s legation to the commander of the Moscow army in Livonia, Afanasy Lavrentievich Ordin‑Nashchokin, in January 1660. An additional task of the legate was to receive a promise of protection of the private estates of the governor of Ducal Prussia, Bogusław Radziwiłł, located in the theatre of war of the imperial armies. Hoffmann fulfilled his task, and Radziwiłł, in order to maintain peaceful relations with Moscow, committed himself to stop the divisions of colonel Georg von Schönaich which supported him in his fight against the Swedes, from engagement in the Lithuanian‑Moscovian conflict.